Komunikasi Persuasif Host Shopee Live pada Kategori Produk Fashion - Wattimena, Grace Heidy Jane Amanda; Larasaty, Past Novel; Afrianti, Riska (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The phenomenon of online shopping through live streaming features has become a new trend in the world of e-commerce, especially on the Shopee Live platform. In this context, the role of the host is very crucial in attracting the audience's interest to make purchases. This study aims to analyze the persuasive communication strategies used by Shopee Live hosts in the fashion product category and their effectiveness in influencing consumer purchasing decisions. A qualitative approach was used with a descriptive study method. Data were obtained through participatory observation in a number of Shopee Live sessions and in-depth interviews with five informants who were active users of the feature. The results of the study showed that Shopee Live hosts used a combination of persuasive communication techniques such as ethos (building personal credibility), pathos (arousing audience emotions), and logos (logical arguments related to product quality and price). The communication style used tends to be interactive, communicative, and adjusted to the characteristics of the fashion target market, namely, young people and active social media users. In addition, the use of relaxed but convincing language with functional, semantic, and thematic diction, through live product demonstrations and providing exclusive promos in real time, has been proven to increase audience engagement and encourage impulsive purchasing actions. This study concludes that persuasive host communication is a strategic element in creating an engaging digital shopping experience that is effective in driving sales conversions